Modern aspects of stock accounting in budgetary organizations - T. L. Leukhina (Вестник университета)
The article considers the problem of current accounting of stocks in public sector organizations through the prism of new standards. As a result, the unity of the system of requirements for accounting of tangible assets was confirmed. The paper reveals the positions of modern scientists and practitioners on the novelty of requirements in the accounting of short-term assets. The author presents the logical scheme of application of norms of accounting of material stocks in the budgetary sphere from the point of view of their subordination. The study generally discloses the criteria for fulfilling the utility of the potential contained in the asset. The article presents and discloses the logical scheme for achieving the utility criterion reflected in the material stock. The author describes the necessity to use inventory as a way to identify signs of attributing assets to stocks or property in storage.